Evaluation of IT Governance for the Inti Accounting System in Retail SMEs using COBIT 2019 - Jesslyn Felicia Elizabeth; Evi Maria (SISTEMASI, 2026)
The utilization of information technology (IT) in retail micro, small, and medium enterprises (SMEs) is essential for improving operational efficiency and service quality. However, limited resources and dependence on external vendors pose significant operational risks. Swalayan Pasar Pagi in Tegal utilizes a locally hosted Inti Accounting System supported by external technical services, making it vulnerable to system downtime and weak internal controls. This study aims to evaluate the governance of the system using the COBIT 2019 framework through an analysis of design factors and the governance system design workflow. The research adopts a qualitative descriptive approach, with data collected through semi-structured interviews, observations, and documentation. The results indicate that the supermarket’s strategy focuses on cost efficiency and improving customer service, with primary objectives including enhancing the quality of management information, optimizing business processes, and increasing operational efficiency. Critical risks identified include vendor dependency, reliance on local server infrastructure, and the absence of internal audits. COBIT 2019 mapping identifies BAI10, EDM05, APO14, and APO12 as priority governance and management objectives. The recommended improvements include the establishment of Service Level Agreements (SLAs), regular data backups, periodic system audits, and training for non-IT staff. This study provides practical contributions to strengthening IT governance in retail SMEs and extends the literature on the application of COBIT 2019 in small enterprises, which remain underexplored. The findings also demonstrate that adapting the COBIT 2019 framework is effective in enhancing operational efficiency and reducing IT-related risks in retail SMEs.